The estimation of the insect fungicidal disinfectant ‘Selest Top’ effect on rice plants - Т. А. Cherepanova; S. V. Bezmutko; V. N. Lelyavskaya (Зерновое хозяйство России)
The current paper has presented the study results (2016–2017) of the products ‘Selest Top’, ‘KS’ (the active ingredients are thiomethoxam (262.5 g/l), difenoconazole (25 g/l) and fludioxonil (25 g/l)) for pre-sowing treatment of rice seeds. The purpose of the work was to estimate the effect of the disinfectant ‘Selest Top’ on the sprouting energy, germination, the processes of initial growth and development of rice plants, to find out the biological efficiency of the product against root rot. There has been carried out a number of laboratory trials to study the effect of the product on sprouting, germination energy of seeds. When conducting a vegetation trial, there was estimated efficiency of the disinfectant against root rot. The test results were compared with the effect of the product ‘Vintsit’ (25 g/l of thiabendazole and 25 g/l of flutriafol). The disinfectant ‘Selest Top’ was used at a rate of 1.0 l/t, 1.5 l/t and 2.0 l/t. It was established that the studied products had no negative effect on sprouting energy and germination of rice seeds. The disinfectant had a positive effect on the length of the rice sprouts and also has a stimulating effect on the plant root system. It was identified that the length of roots increased on 2.2–3.0 cm (7 days) and 1.0–3.8 cm (14 days). There was established that the product had a high biological efficiency against root rot at all stages of rice development. The maximum indicators were obtained at a rate of 1.5 l/t with 57.3% (complete sprouts), 57.2% (panicle formation) and 37.2% (milky-wax ripeness). Under the agroclimatic conditions of Primorsky Krai, the pre-sowing seed treatment with the product ‘Selest Top’ is justified due to the high biological efficiency and increased plant resistance to root rot pathogens.